1986
DOI: 10.1128/mcb.6.8.2990
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic effects of the proto-oncogene and oncogene forms of c-H-ras DNA in human diploid fibroblasts.

Abstract: Nuclear microinjection of c-H-ras DNA induced DNA synthesis in reversibly nonproliferating quiescent human cells. The proto-oncogene and oncogene forms were equally effective inducers. In contrast, c-H-ras DNA either alone or in combination with the adenovirus E1A gene did not cause terminally nondividing senescent cells to synthesize DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Assuming that these differences in expression correlate with the levels of gene product, our results are in agreement with the current thought that the cellular functions of the p2ls encoded by H-ras, K-ras, and N-ras are indeed different, as their products seem to be required in different amounts and at different times in a tissue-specific manner. Although p21 seems to be involved in cell proliferation (23,27), in this study we showed that H-ras is also expressed in mouse brain and muscle at its highest levels, where cell division is minimal. This suggests a role for ras genes which is not restricted to proliferation.…”
mentioning
confidence: 82%
“…Assuming that these differences in expression correlate with the levels of gene product, our results are in agreement with the current thought that the cellular functions of the p2ls encoded by H-ras, K-ras, and N-ras are indeed different, as their products seem to be required in different amounts and at different times in a tissue-specific manner. Although p21 seems to be involved in cell proliferation (23,27), in this study we showed that H-ras is also expressed in mouse brain and muscle at its highest levels, where cell division is minimal. This suggests a role for ras genes which is not restricted to proliferation.…”
mentioning
confidence: 82%
“…H-ras protein can induce DNA synthesis (21) or differentiation (1) in different cell types. In Xenopus oocytes, ras protein can induce meiosis (2).…”
Section: Discussionmentioning
confidence: 99%
“…Log-phase, quiescent, and senescent HCA2 ( foreskinderived fibroblast, also called MJ90) and IMR90 (lung-derived fibroblast) cells were cultured as described previously (19). Confluent cultures of young cells, population doubling (PD) 34 or lower, were made quiescent by incubation in 1% serum-containing medium for at least 7 days, conditions we have established previously and have confirmed typically result in <15% cells labeling after a 48-hour continuous bromodeoxyuridine exposure.…”
Section: Methodsmentioning
confidence: 99%